A comparative Pc1 case study applying two modes of ionospheric Alfvén resonator modeling - Prikner, K. (Karel); Feygin, F. Z.; Raita, T. (Studia Geophysica et Geodaetica, 2010)
The case study of four Pc1 subauroral pulsation events from Finland has been carried out on the basis of the full-wave numerical method. This method has been applied to simultaneous Scandinavian EISCAT radar measurements of the ionospheric plasma parameters and their vertical (altitude) profiles have been utilized. Two alternative plasma profiles with different ion composition displays have been put to the test. A comparison between both types of the modeled ionospheric Alfven resonator (IAR) ground signal frequency response and the frequency range of the Pc1 signal records has been studied. The results of the applied method can illustrate possible quiescent or disturbance changes in the upper ionosphere above the dense F2 layer.